Orange Zinc Germanate with Metallic GeGe Bonds as a Chromophore‐Like Center for Visible‐Light‐Driven Water Splitting. Issue 39 (20th August 2015) - Qian, Ling; Chen, Jian Fu; Li, Yu Hang; Wu, Long; Wang, Hai Feng; Chen, Ai Ping; Hu, P.; Zheng, Li Rong; Yang, Hua Gui
Abstract: The efficiency of solar‐energy‐conversion devices depends on the absorption region and intensity of the photon collectors. Organic chromophores, which have been widely stabilized on inorganic semiconductors for light trapping, are limited by the interface between the chromophore and semiconductor. Herein we report a novel orange zinc germanate (Zn‐Ge‐O) with a chromophore‐like structure, by which the absorption region can be dramatically expanded. Structural characterizations and theoretical calculations together reveal that the origin of visible‐light response can be attributed to the unusual metallic GeGe bonds which act in a similar way to organic chromophores. Benefiting from the enhanced light harvest, the orange Zn‐Ge‐O demonstrates superior capacity for solar‐driven hydrogen production. Abstract : Ge up : Unexpectedly a Zn‐Ge‐O semiconductor responds to visible light. It is shown that it contains a built‐in chromophore‐like structure. By a combination of systematic characterizations and theoretical calculations, the origin of the visible‐light response can be attributed to the unusual presence of metallic GeGe bonds which act in a similar way to organic chromophores.